A hybrid approach for Arabic named entity disambiguation - AL-Smadi, M.; Talafha, B.; Qawasmeh, O.; Alandoli, M.; Hussien, W.; Guetl, Christian (ACM, 2015)
This research aims at tackling the problem of Arabic Named Entity Disambiguation (NED) through an enhanced approach of information extraction from DBpedia and Arabic Wikipedia using query label expansion and text similarity techniques.